Irrational Blame. - Pickard, H (2013)
I clarify some ambiguities in blame-talk and argue that blame's potential for irrationality and propensity to sting vitiates accounts of blame that identify it with consciously accessible, personal-level judgements or beliefs. Drawing on the cognitive psychology of emotion and appraisal theory, I develop an account of blame that accommodates these features. I suggest that blame consists in a range of hostile, negative first-order emotions, towards which the blamer has a specific, accompanying second-order attitude, namely, a feeling of entitlement - a feeling that these hostile, negative first-order emotions are what the blamed object deserves.